EVALUASI RANTAI PERMINTAAN WISATA DALAM PERENCANAAN PEMBANGUNAN EKOWISATA DI KAWASAN WISATA CIBODAS, JAWA BARAT - Tutut Sunarminto; Dudung Darusman; Hadi S Alikodra; Ricky Avenzora (Media Konservasi, 2014)
In order to increase the quality of ecotourism experiences on Cibodas Ecotourism Destination Area, a reasearch on demand-chain have been done. A set of questionaires has been distributed for getting better information about motives, percepstion and opinion of the ecotourist; by using the Likert score. The result shows that as long as the ecotourists still have a chance to take a picnic, gathering and social contact in the area, most of them are not yet interest on quality of activities. Since the characteristic of impassivity tourist very clear seen amongst the ecotourist in the area, therefore it is important to apply the personal marketing concept in handling the ecotourist.    Keywords: Cibodas, Demand Chain, Ecotourism, West Java, Personal Marketing.